American assassin [videorecording (DVD)] - O'Brien, Dylan, 1991-; Keaton, Michael, 1951-; Lathan, Sanaa; Flynn, Vince, 1966-2013 (Lionsgate, 2017)
After the death of his girlfriend at the hands of Islamic terrorists, Mitch Rapp is drawn into the world of counterterrorism, mentored by tough-as-nails former U.S. Navy SEAL Stan Hurley.